Determination of audit activity in modern conditions - Siketina, Natalya Hennadievna (Leipzig University, 2018)
The task of compulsory audit of financial statements is the provision of reasonable assurance that is accepted and performed by the entity in accordance with the requirements of this Law and international standards of audit by checking the financial statements or consolidated financial statements in order to express an independent opinion of the auditor on its compliance with all significant aspects and compliance with the requirements of international financial reporting standards or national accounting (statutory) standards and laws of Ukraine.
Keywords: accounting; audit activity; financial control